Investigation of TiO2 thin films prepared via solgel dip coating technique for high absorbance / Muhammad Nor Azreen Abd Halim - Abd Halim, Muhammad Nor Azreen (2016)
In this study, a Titanium Dioxide (TiCte) thin films layers was deposited onto glass substrate for high absorbance by using sol gel dip coating technique. The glass substrate were coated with several layers of TiCte thin films which is 1, 3, 5, 7 and 9 layers. The characterization of the optical and physical properties of TiCte thin film coated layers of the glass substrate were characterized using Field Emission Scanning Electron Microscopy (FESEM) for surface morphology, UV-VIS spectrometer for transmittance and absorbance, Surface Profiler for the thin films thickness and Atomic Force Microscope (AFM) for surface topology of the films. The end result shows that by increasing the number of thin films layers will increase the optical absorbance and thickness of the TiCte thin films.